Achieving SDG 2 in east java: Agriculture and food security office’s role - Hariyanti, Carelia Pradita (Glocal Society Journal, 2025)
The global food security crisis, exacerbated by climate change, conflicts, and pandemics, has led to millions suffering from hunger and malnutrition. In Indonesia, the prevalence of stunting remains high, necessitating urgent action to achieve Sustainable Development Goal (SDG) 2, which aims for "Zero Hunger" by 2030. This study aims to explore the strategies employed by the East Java Agriculture and Food Security Agency to address food security challenges and achieve SDG 2. A descriptive qualitative approach was utilized, involving in-depth interviews with agency personnel and literature reviews. The agency has implemented several initiatives, including the GENIUS program to enhance nutrition among school children, the Cheap Food Movement to stabilize food prices, and the B2SA program to promote diverse and nutritious food consumption. These efforts aim to improve food access, reduce stunting, and raise awareness about nutrition. The East Java Agriculture and Food Security Agency plays a pivotal role in addressing food security issues, contributing significantly to the achievement of SDG 2 through targeted programs that enhance food availability, affordability, and nutritional education.